ТЕРМІЧНИЙ АНАЛІЗ КОМПОЗИТНОГО ПАЛИВА - Sniezhkin, Yu.F.; Petrova, Zh.O.; Mykhailyk, V.A.; Petrov, А.І.; Novikova, Yu.P. (Institute of Engineering Thermophysics of NAS of Ukraine, 2023)
One of the main problems of the modern world is the search for and supply of renewable energy resources that could compete with oil and natural gas. In recent years, humanity has entered the era of biotechnology, which uses renewable raw materials for the production of energy and materials. The energy industry considers biofuel and peat as alternative types of fuel. Biofuel is a renewable type of energy, its main advantage is environmental friendliness, and modern production methods make it possible to obtain fuel samples that often exceed traditional samples in terms of their characteristics and cost. In Ukraine, there are large deposits of peat, which belongs to solid biofuel, and which is also used as fertilizer. Today, peat, which contains a large number of humic substances, is used more as fertilizer for agriculture than as fuel. These substances are not water-soluble and become so only in an alkaline environment. If humic substances are extracted from it, and the residue after extraction is burned, then this unique natural resource can be used more rationally. The paper presents a study of thermal analysis of composite fuel based on the solid residue of peat after extraction of humic substances and corn stalks from it. Composite fuel and its components were investigated using the methods of thermogravimetry and differential thermal analysis: crushed solid residue of milled peat after extraction of humic substances and corn stalks in an alkaline medium, and temperature intervals and rates of dehydration, thermal decomposition of organic and mineral substances, humidity and ash content were determined. The conditional thermal effect of thermal decomposition of organic substances of composite fuel and its components is estimated. It was found that the conditional thermal effect of the thermal decomposition of organic substances of the composite fuel is higher than the conditional thermal effect of the fuel components. It is shown that the created composite fuel is an effective alternative type of fuel, the cost per unit of energy of which is lower than that of traditional fuels.